Taẕkirah-yi ʻAllāmah Mīr ʻAbduljalīl Bilgrāmī, mausūm bih, Ḥayāt-i Jalīl - Ṣamdanī, Sayyid Maqbūl Aḥmad (SAMP early 20th-century Indian books project, 1929)
Life and works of Mīr ʻAbduljalīl Bilgrāmī, Urdu poet.